Addressing ADL ability in people with poststroke cognitive impairments: A Danish survey of clinical practice - E. Ghaziani; S. S. Christensen; C. H. Arens; E. E. Wæhrens (Scandinavian Journal of Occupational Therapy)
Background In Denmark, stroke represents a leading disability cause. While people with difficulties in performing activities of daily living (ADL) due to poststroke cognitive impairments are often referred to occupational therapy, limited knowledge is available on the nature of these services.Aim/Objective To explore how Danish occupational therapists describe their practice when addressing decreased ADL ability in people with poststroke cognitive impairments in hospital and municipality settings.Material and Methods National, cross-sectorial, web-based public survey.Results 244 occupational therapists accessed the survey; 172 were included in the analysis. Most respondents could indicate the theory guiding their reasoning; half used standardised assessments. Regarding intervention, restorative and acquisitional models were preferred; specific strategies were identified. Intensity: 30-45 min 3-4 times/week in hospitals; 30-60 min 1-2 times/week in municipalities.Conclusions Therapists report to be guided by theory in their reasoning. Standardised assessments are used to a higher extend than previously reported. Still, the results invite critical reflections on correct use of assessment instruments, content and intensity of interventions, and how therapists keep themselves updated.Significance The results document the need for practice improvements and may inform the definition of standard care in future trials.